A Superhydrophobic Smart Coating for Flexible and Wearable Sensing Electronics. Issue 43 (22nd September 2017) - Li, Lianhui; Bai, Yuanyuan; Li, Lili; Wang, Shuqi; Zhang, Ting
Abstract: Superhydrophobic surfaces have shown versatile applications in waterproofing, self‐cleaning, drag reduction, selective absorption, etc. The most convenient and universally applicable approach to forming superhydrophobic surfaces is by coating; however, currently, superhydrophobic, smart coatings with flexibility and multiple functions for wearable sensing electronics are not yet reported. Here, a highly flexible multifunctional smart coating is fabricated by spray‐coating multiwalled carbon nanotubes dispersed in a thermoplastic elastomer solution, followed by treatment with ethanol. The coatings not only endow various substrate materials with superhydrophobic surfaces, but can also respond to stretching, bending, and torsion—a property useful for flexible sensor applications. The coatings show superior sensitivity (gauge factor of 5.4–80), high resolution (1° of bending), a fast response time (<8 ms), a stable response over 5000 stretching–relaxing cycles, and wide sensing ranges (stretching: over 76%, bending: 0°–140°, torsion: 0–350 rad m −1 ). Moreover, multifunctional coatings with thicknesses of only 1 µm can be directly applied to clothing for full‐range and real‐time detection of human motions, which also show extreme repellency to water, acid, and alkali, which helps the sensors to work under wet and corrosive conditions. Abstract : A multifunctional, stretchable smart coating is fabricated by spray‐coating multiwalled carbon nanotubes dispersed in a thermoplastic elastomer solution, followed by treatment with ethanol. The coatings are superhydrophobic and piezoresistive, for water repellency and wearable strain‐sensor applications. The extreme repellency to water, UV, acid, and alkali characteristics of the coating endow highly sensitive and stable sensing performance under wet/corrosive conditions.